2022
DOI: 10.3390/pharmaceutics14030485
|View full text |Cite
|
Sign up to set email alerts
|

Wound Dressing: Combination of Acacia Gum/PVP/Cyclic Dextrin in Bioadhesive Patches Loaded with Grape Seed Extract

Abstract: The success of wound treatment is conditioned by the combination of both suitable active ingredients and formulation. Grape seed extract (GSE), a waste by-product obtained by grape processing, is a natural source rich in many phenolic compounds responsible for antioxidant, anti-inflammatory, and antimicrobial activities and for this reason useful to be used in a wound care product. Bioadhesive polymeric patches have been realized by combining acacia gum (AG) and polyvinylpyrrolidone (PVP). Prototypes were prep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 46 publications
0
8
0
Order By: Relevance
“…Our previous studies demonstrated that GSE and PE could be released from GO-based aerogels , and PLA/GEL electrospun nanofibers in a rather controlled fashion, achieving release rates close to 16% after 35 days of incubation. More recently, Pagano et al investigated the release profiles of GSE loaded in acacia gum/polyvinyl­pyrrolidone/cyclic dextrin patches. They showed that GSE can be released in a sustained manner, reaching concentrations close to 30% after 48 h incubation.…”
Section: Resultsmentioning
confidence: 99%
“…Our previous studies demonstrated that GSE and PE could be released from GO-based aerogels , and PLA/GEL electrospun nanofibers in a rather controlled fashion, achieving release rates close to 16% after 35 days of incubation. More recently, Pagano et al investigated the release profiles of GSE loaded in acacia gum/polyvinyl­pyrrolidone/cyclic dextrin patches. They showed that GSE can be released in a sustained manner, reaching concentrations close to 30% after 48 h incubation.…”
Section: Resultsmentioning
confidence: 99%
“…According to Ejaz et al, 23 wound contraction accounts around 88% of the healing process. The total phenols, flavonoids, and tannins found in the grape seed have been shown to be important for wound healing and antimicrobial activities 24 . Also, topical use of grapes seed hydroethanolic extract cause decreases in healing period 25 .…”
Section: Discussionmentioning
confidence: 99%
“…Cell viability was evaluated by MTT test [ 32 , 33 , 34 ]. The experiments were performed on HaCaT cells (human immortalized keratinocyte cell line), purchased from I.Z.S.L.E.R.…”
Section: Methodsmentioning
confidence: 99%